Convenient synthesis of functionalized pyrrolo[3, 4-b]pyridines and pyrrolo[3, 4-b]quinolines via three-component reactions. Issue 42 (12th April 2016) - Jiang, Yan-Hong; Xiao, Man; Yan, Chao-Guo
Abstract : A simple protocol for convenient construction of pyrrolo[3, 4- b ]pyridine skeleton was successfully developed by base promoted three-component reaction of β-enamino imide, aromatic aldehydes and malononitrile as well as its ester and amide derivatives. Abstract : A simple protocol for convenient construction of pyrrolo[3, 4- b ]pyridine skeleton was successfully developed by base promoted three-component reaction of β-enamino imide, aromatic aldehydes and malononitrile as well as its ester and amide derivatives. The similar three-component reaction of β-enamino imide, aromatic aldehydes and cyclic diketones such as dimedone and cyclohexane-1, 3-dione afforded functionalized pyrrolo[3, 4- b ]quinolines in good yields.